Philosophical anthropology of K. Marx - Liahchylin, Anatoli A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
Based on the statements of K. Marx, the logic of his understanding of the essence of man is being built. It is shown that the nature of human existence in K. Marx’s understanding is variable depending on socio-economic conditions. In the context of understanding the essence of man, the Marxian concept of the destiny of man was formed.